Pregnane X Receptor Is SUMOylated to Repress the Inflammatory Response - Hu, Gang (The American Society for Pharmacology and Experimental Therapeutics, 2010)
Long-term treatment of patients with the macrolide antibiotic and prototypical activator of pregnane X receptor (PXR) rifampicin (Rif) inhibits the inflammatory response in liver. We show here that activation of the inflammatory response in hepatocytes strongly modulates SUMOylation of ligand-bound PXR. We provide evidence that the SUMOylated PXR contains SUMO3 chains, and feedback represses the immune response in hepatocytes. This information represents the first step in developing novel pharmaceutical strategies to treat inflammatory liver disease and prevent adverse drug reactions in patients experiencing acute or systemic inflammation. These studies also provide a molecular rationale for constructing a novel paradigm that uniquely defines the molecular basis of the interface between PXR-mediated gene activation, drug metabolism, and inflammation.